Procedural features of consideration of certain categories - Seidimbek, А.А.; Alenov, М.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article conducts a study of the procedural features of the consideration of certain categories of civil cases. The specifics of various categories of cases considered in civil proceedings require special attention and timely changes to the legislation to ensure timely and fair resolution of civil disputes. It has been determined that the legal mechanism for resolving civil disputes is built on a well-known two-element basis: pre-trial/extrajudicial, judicial. Ignoring this simple rule leads to overloading of courts, which does not contribute to the quality of their work. Special attention is paid to the study of issues of consideration of labour disputes. The problem of the timing of preparation and consideration of cases, which was significantly changed when the new Civil Procedure Code of the Republic of Kazakhstan was adopted on October 31, 2015, is disclosed in detail. The method of simplifying the resolution of civil disputes presented in the Code of Civil Procedure does not fully consider the nature and characteristics of cases of disputes arising from labour relations. As a result of the article, recommendations are proposed aimed at developing for certain categories of cases, in particular cases arising from labour relations, a separate procedural model for their resolution. Specifically in labour disputes, it seems possible to provide for shorter terms for consideration of the case. It is also possible to introduce special procedures to expedite the processing of cases depending on their industry category.